2019
DOI: 10.24912/jmishumsen.v3i2.3353.2019
|View full text |Cite
|
Sign up to set email alerts
|

Perilaku Kerja Inovatif ditinjau dari Modal Psikologis, Tuntutan Kerja, dan Sumber Daya Pekerjaan

Abstract: ABSTRAKPenelitian ini membahas mengenai hubungan modal psikologis, tuntutan kerja, sumber daya pekerjaan dan perilaku kerja inovatif pada widyaiswara. Tujuan dari penelitian ini adalah untuk melihat variabel mana antara modal psikologis, tuntutan kerja, sumber daya pekerjaan, yang menjelaskan perilaku kerja inovatif. Partisipan pada penelitian ini adalah Widyaiswara pada Kementerian Kesehatan. Berdasarkan path analysis, hasil penelitian menunjukan bahwa perilaku kerja inovatif paling dijelaskan oleh sumber day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
2
0
1
Order By: Relevance
“…This assertion follows the opinion of Bakker and Demerouti (2008) support from the work environment, such as feedback and knowledge-sharing, can make healthcare workers feel enthusiastic and appreciate their work. Because the presence of job resources can reduce the job demands of healthcare workers, and resources can also predict the emergence of innovative work behavior (Hasanah et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This assertion follows the opinion of Bakker and Demerouti (2008) support from the work environment, such as feedback and knowledge-sharing, can make healthcare workers feel enthusiastic and appreciate their work. Because the presence of job resources can reduce the job demands of healthcare workers, and resources can also predict the emergence of innovative work behavior (Hasanah et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Teamwork, leadership style, and support from colleagues and superiors, such as providing constructive feedback, are included in the social environment factors that can influence the emergence of innovative work behavior. Hasanah et al (2019) stated that work resources and demands correlate with innovative work behavior. From the two antecedents, work resources are the better predictor of innovative work behavior.…”
Section: Introductionmentioning
confidence: 99%
“…This can make individuals established new skills so as to innovate (Dediu et al, 2018). The research results from Hasanah et al (2019) indicates that mostly employees tends to be more innovative in facing higher demands when they provide by high job resources. This research was conducted at the Widyaiswara of the Ministry of Health which showed a significant impact from work demands and work resources towards innovative behavior.…”
Section: Creativitymentioning
confidence: 98%
“…Penelitian yang dilakukan oleh Rahimah, et al, (2018) mengemukakan apabila moralitas individu signifikan mempunyai pengaruh dalam mencegah adanya penyelewangan anggaran dana desa. Lemahnya kapabilitas dan moralitas setiap aparatur desa juga menjadi penyebab rawannya tata kelola keuangan dana desa yang lemah, kurang transparan dan partisipatif terhadap masyarakat desa (Hasanah, et al, 2019). Riset sebelumnya yang dilakukan oleh Dewi, Yuniasanti & Prahara, (2017) juga menyatakan bahwa perilaku inovasi dalam organisasi adalah satu diantara penyebab yang mendukung keberhasilan sebuah organisasi dalam tata kelola organisasi maupun aspek didalamnya.…”
Section: Gambar 2 Jumlah Dana Desa Kecbalongbendo Tahun 2019-2022unclassified